COKE DUST FORMATION IN THE OIL REFINING PROCESS AND ITS IMPACT ON THE ENVIRONMENT AND WORKERS' HEALTH (Modern American Journal of Medical and Health Sciences, 2026)
Objective: To identify the sources of coke dust formation, assess its chemical composition and physico-hygienic characteristics, and evaluate the impact on worker health and the environment at the Fergana Oil Refinery (FNPZ).Methods: A multidisciplinary methodological approach was applied: gravimetry, aspiration, laser diffraction, computer spirometry (FVC, FEV₁), ECG monitoring (heart rate), skin thermometry at proximal and distal body points, and variance statistics. Workers of 10 leading occupational groups at the AVT 21.10/600 unit were examined.Results: Dust dispersion analysis revealed: PM₁₀ fraction >70%, PM₂.₅ >30%, enabling deep alveolar penetration. Extreme hydrophobicity of coke dust (93% amorphous carbon) was identified, rendering water-based dust suppression ineffective. Initial dust concentration reached 7.2–8.0 mg/m³ against a MAC of 6.0 mg/m³. Working conditions were classified as hazardous classes 3.1 and 3.2. Cardiovascular strain was documented: heart rate, stroke and minute volumes increased by up to 22%. Following the implementation of the preventive complex, concentration stabilised at 3.9 mg/m³ — reliably below MAC (p